Prediction of the phase distribution of diesel/CNG bubbly flow in a horizontal pipe under the influence of a magnetic field - Wahhab, H.A.A. (Korean Society of Mechanical Engineers, 2017)
This paper describes an analytical study of the magneto hydrodynamics of small CNG bubbles in laminar horizontal diesel flow under the influence of a magnetic field. The investigation is based on experiments carried out to identify the effect of varying the magnetic field intensity on the trajectory, the formation of bubbles and their shape and velocity in the flow. Different images at different positions downstream of the CNG bubbles injection point were captured by a high speed camera and analyzed by image processing techniques provided information on bubble velocity, bubbles size, spatial location and gas area fraction as a function of changing the magnetic field intensity. The outcomes confirmed that CNG bubbles under magnetic field grow up vertically to an elliptical shape in the diesel phase with a mean diameter about twice that of the original bubble. It was also noticed that the velocity of the CNG bubbles decreased as the strength of the magnetic field increased. © 2017, The Korean Society of Mechanical Engineers and Springer-Verlag GmbH Germany, part of Springer Nature.